Exploring the chemical profile, antioxidant, in vivo anti-inflammatory and gastroprotective properties of watermelon (Citrullus lanatus thunb.) in rats - Amel Bouaziz; Saliha Djidel; Assia Bentahar; Nihed Barghout; Seddik Khennouf; Saliha Dahamna (Revista Científica)
Citrullus lanatus thunb. (watermelon) belonging to the Curcubitaceae family, is the most important crops worldwide. The present work aims to estimate the polyphenolic content, anti-inflammatory and antiulcer properties, in addition to the antioxidant activity of ethanolic extract of watermelon flesh fruit. The ethanolic extract of watermelon fruit contains secondary metabolites, polyphenols, flavonoids and tannins. Reducing power test and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) scavenging assay were used to measure the antioxidant activity. In the two tests that were examined, watermelon ethanolic extract demonstrated a potent antioxidant potential. Pretreatment of rats with watermelon extract at the doses of 200 and 600 mg·kg-1 demonstrated significant anti-inflammatory effect and decreased carrageenan induced paw edema, with inhibition percentages of 57.24 ± 3.18 and 69.00 ± 2.80%, respectively. However, the doses 50, 200, and 600 mg·kg-1 of watermelon extract pretreated to rats reduced gastric mucosal injury on ethanol induced acute gastric ulcer with percentages protection of 75.01 ± 0.77, 92.38 ± 2.98 and 95.01 ± 0.81% compared to omeprazole (95.92%). This study revealed that watermelon fruit consumption could be a promising anti-inflammatory and gastroprotective agents.